GOTHAM CITY SEBAGAI PERSENTASI KOTA BANDUNG : KAJIAN KERESAHAN MASYARAKAT TERHADAP KENAKALAN REMAJA TONGKRONGAN “NGABERS” - Gymnastiar, Iman Ahmad; Hufad, Achmad; Wahyuni, Sri; Bagus, Mochamad Rizky (Jurnal Analisa Sosiologi, 2024)
The Ngabers youth group is one of the group-based juvenile delinquency cases that causes unrest and threats in the community because the presence of the Ngabers youth group with all its activities such as rolling, arrogance driving, and other delinquency activities can be detrimental to road users and the people of Bandung City itself. This phenomenon creates an analogy for the city of Bandung to be similar to a fictional city, namely Gotham City. Gotham City is a fictional city full of darkness and crime that is contained in the storylines of films and comics produced by DC Comics. This writing uses a qualitative approach with the case study method. Through a data collection process, the results obtained from the research are: (1) Bandung City and Gotham City have similar aspects, namely criminal characteristics and different aspects as well. (2) The factors that cause youth to join the Ngabers group are internal factors and external factors. (3) The general description of the behavior/activities carried out by young ngabers includes disturbing activities such as rolling, arrogance driving, abusing illegal drugs, and drinking liquor and there are also supporting activities such as street photography. The solution from the police that has been outlined is action against noisy exhausts, night patrols, to guidance by the Criminal Investigation Unit. However, this solution is not effective considering that community participation is still not sensitive and communicative.